Sosialisasi Budaya Kesenian Calung Salakadomas di Dusun Kelewih Desa Saguling Kecamatan Baregbeg Kabupaten Ciamis - Octavia, Angelica Nenaputri; Putri, Fahira Anindya; Ramdani, Gilang; Robi, Robi; Setiadi, Budi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is behind the background of the influence of foreign cultural transformation which is today a real threat to traditional culture. This can lead to the weakening of the values of traditional cultural art and have a major impact on the survival of traditional art in society, one of which is the anti-traditional art. Calung is a traditional musical instrument commonly played in popular performances in society, but the popularity of Calung is now declining due to the influence of foreign cultural transformation. This is supported by public surveys that show that foreign musical instruments are more popular and popular with the general public than traditional music instruments. This research aims to introduce and expand public understanding of the traditional cultural wealth of one of the Traditional Art of Calung that exists in the village of Saguling Prefecture Baregbeg district of Ciamis. The method used is qualitative descriptive method with the type of case study. This investigation was carried out against the figures of the academic anti-artists. The data collection techniques used are observations, interviews and documentation. The results of this study show that there are still societies that maintain the traditional anti-art in the midst of evolving times that are constantly changing.